Trematodes of Paramphistomatidae Infecting Domestic Ruminants - Tarun Shankar Nath (Department of Parasitology, College of Veterinary and Animal Sciences, 1987)
The thesis embodied the results of an investigation on the prevalence of amphistome infection and their specific identity in different domestic ruminants (cattle, buffaloes, sheep and goats) of Kerala state.